What are the implications of climate change for trans-Atlantic aircraft routing and flight time?. (August 2016) - Irvine, Emma A.; Shine, Keith P.; Stringer, Marc A.
Highlights: We assess the impact of climate change on upper-level winds and aircraft routing. Climate models agree on a strengthened and more northerly north Atlantic jet by 2100. Daily variations in the north Atlantic jet are larger than these long-term changes. Future minor changes to trans-Atlantic flight time of order 1 min by 2100. Projected wind changes will have minimal impact on flight location and duration. Abstract: The effect of wind changes on aircraft routing has been identified as a potential impact of climate change on aviation. This is of particular interest for trans-Atlantic flights, where the pattern of upper-level winds over the north Atlantic, in particular the location and strength of the jet stream, strongly influences both the optimal flight route and the resulting flight time. Eastbound trans-Atlantic flights can often be routed to take advantage of the strong tailwinds in the jet stream, shortening the flight time and reducing fuel consumption. Here we investigate the impact of climate change on upper-level winds over the north Atlantic, using five climate model simulations from the Fifth Coupled Model Intercomparison Project, considering a high greenhouse-gas emissions scenario. The impact on aircraft routing and flight time are quantified using flight routing software. The climate models agree that the jet stream will be on average located 1° further north, with a small increase in mean strength, by 2100. However daily variations in both its location and speed are significantly larger than the magnitude of any changes due to climate change. The net effect of climate change on trans-Atlantic aircraft routes is small; in the annual-mean eastbound routes are 1 min shorter and located further north and westbound routes are 1 min longer and more spread out around the great circle. There are, however, seasonal variations; route time changes are larger in winter, while in summer both eastbound and westbound route times increase.